Land Suitability and Agricultural Technology for Rice Cultivation on Tidal Lowland Reclamation in South Sumatra - Momon Sodik Imanudin; Probowati Sulistiyani; M Edi Armanto; A Madjid; Anton Saputra (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2021)
Tidal lowland is one of the potential lands for agriculture that is found very widely in coastal areas of South Sumatra. There are about 400,000 hectares (ha) was reclaimed for agriculture purpose. However, in many parts, the rice production is still low (<3 ton/ha), mainly in the high part of hydrotopography class (Type C) that the tidewater could not possibly irrigate the land. This study aimed to evaluate the level of actual and potential suitability of tidal swamps for rice plants. This research has been carried out in Bandar Jaya Village, Air Sugihan Subdistrict, Ogan Komering Ilir Regency. This research used a survey level method with very detailed (intensive) with a scale of 1:6,000 covering a research area of 16 ha. The results showed that actual suitability for rice plants in the study site is N-n with an area of 5 ha and N-f, n with an area of 11 ha with limiting factors of soil pH and P nutrient. The potential land suitability class for rice plants in the study location is S3-n with an area of 5 ha and S3-f, n with an area of 11 ha. Land quality improvement was done by using the lime application and control water table at a depth of at least 10 cm from the soil surface during rice growth. Rainwater should be retained in the tertiary block as much as possible to fulfill crop water requirements. Setting the planting time (November-January) and balanced fertilization will be able to increase the land suitability class to S1 (highly suitable).